Economic links among Callao, Arica and Valparaiso during the Bolivian-Peruvian Confederation 1836- 1839 - Mazzeo, Cristina (2018)
The objective is to analyze the relationship among the main ports of Valparaiso and Callao with the intermediate ports of the southern Andes during the Bolivian-Peruvian Confederation. It shows how despite the political conflicts unleashed by the war against the Confederation, the trade carried out by important foreign mercantile companies installed in Valparaiso connected the ports of Arica, Islay and Cobija, which acted as links with the great international trade. The new group of merchants created a closely linked merchant network in the region. Based on the documentation of Bolivia, Chile and Peru customs, it addresses the extent to which the competition of interests between the port of Arica and Cobija was one of the reasons for the war against the Confederation.